Hydrochars from industrial macroalgae "Gelidium Sesquipedale" biomass wastes. (March 2019) - Méndez, A.; Gascó, G.; Ruiz, B.; Fuente, E.
Graphical abstract: Highlights: HTC technology in the upgrading and sustainable management of macroalgae waste. HTC increases thermal stability and the HHV of macroalgae waste-based hydrochars. HTC favours the progressive aromatization and decarboxylation of hydrochars. HTC retains to a large extent the vegetal structure of macroalgae industrial waste. Hydrochars are essentially meso-macroporous and such porosity is favored with HTC. Abstract: Macroalgae wastes from the Agar–Agar industry were used as a feedstock to obtain hydrochars by means of hydrothermal carbonization. The effect of temperature (200 °C and 230 °C) and time (2 h and 6 h) on the yield, higher heating value (HHV) and chemical-morphological-textural properties of the hydrochars was studied. The carbon content and the higher heating value were observed to increase with the hydrothermal carbonization. The hydrochars yields (up to 60%) were much higher than yields obtained using conventional char (27.5–33.5%). The hydrochar obtained at 230 °C and after 6 h showed a HHV of 23.25 MJ/kg, which is similar to that of lignite HHV. The H/C and O/C atomic ratios decreased as a consequence of the dehydration and decarboxilation reactions. Hydrothermal carbonization barely changed the vegetal structure of the macroalgae waste. The hydrochars were found to be essentially meso-macroporous with average pore sizes of up to 110.5 nm.